2012
DOI: 10.1002/ajim.22085
|View full text |Cite
|
Sign up to set email alerts
|

The Upper Midwest Health Study: Industry and occupation of glioma cases and controls

Abstract: Background Understanding glioma etiology requires determining which environmental factors are associated with glioma. Upper Midwest Health Study case–control participant work histories collected 1995–1998 were evaluated for occupational associations with glioma. “Exposures of interest” from our study protocol comprise our a priori hypotheses. Materials and Methods Year-long or longer jobs for 1,973 participants were assigned Standard Occupational Classifications (SOC) and Standard Industrial Classifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…141,142 However, in contrast to previous studies, 58,142 -144 there was no association between farming and glioma risk in the Upper Midwest Health Study (UMHS) conducted between 1995 and 1998. 145 The difference in findings might be explained by differences in the study populations: UMHS included nonurban controls with farming as their longest job, whereas De Roos's study 143 included only controls with at least 5 years of farm experience. In both the UMHS and a Canadian study, being an engineer, an architect, or a surveyor was associated with an increased risk of glioma.…”
Section: Occupational Chemical Exposuresmentioning
confidence: 99%
“…141,142 However, in contrast to previous studies, 58,142 -144 there was no association between farming and glioma risk in the Upper Midwest Health Study (UMHS) conducted between 1995 and 1998. 145 The difference in findings might be explained by differences in the study populations: UMHS included nonurban controls with farming as their longest job, whereas De Roos's study 143 included only controls with at least 5 years of farm experience. In both the UMHS and a Canadian study, being an engineer, an architect, or a surveyor was associated with an increased risk of glioma.…”
Section: Occupational Chemical Exposuresmentioning
confidence: 99%
“…[ 26 ] Their publication years ranged from 1989 to 2011. Among the studies, 6 were conducted in the USA, [ 9 , 20 , 25 , 27 , 28 , 31 ] 3 in Sweden, [ 10 , 12 , 24 ] 2 in New Zealand, [ 11 , 22 ] 2 in Uruguay, [ 29 , 30 ] and 1 in the Netherlands. [ 13 ] Moreover, 1 was conducted in 10 participating centers in the following locations: Denmark, Italy, the Netherlands, Norway, Spain, Sweden, UK, Germany, Greece, and France.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 11 studies were of high methodological quality, [ 9 , 10 , 13 , 20 , 22 , 23 , 26 28 , 30 , 31 ] 3 studies [ 11 , 24 , 29 ] were of moderate quality, and 3 studies [ 12 , 21 , 25 ] were of poor quality based on the modified NOS. The main deficiency was the selection bias related to the insufficient adjustment of confounding factors among the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…In the Upper Midwest Health Study (UMHS), Ruder et al (2012) developed, a priori, a list of 21 exposures of interest identified from the literature as being potentially related to glioma risk. These studies are complicated by small numbers and the difficulties of segregating one of the many agents in the workplace, as well as other inherent problems in retrospective studies.…”
Section: Industry and Occupationmentioning
confidence: 99%